Mitochondrial uncoupling proteins in mammals and plants - Borecký, J; Maia, I G; Arruda, P (Bioscience reports, 2001)
Uncoupling proteins (UCPs) belong to a distinct cluster of the mitochondrial anion carrier family. Up to five different uncoupling protein types were found in mitochondria of mammals and plants, and recently in fishes, fungi and protozoa. They exhibit a significantly conserved structure with several motifs specific to either the whole cluster or protein type. Uncoupling proteins, as well as the whole mitochondrial anion carrier gene family, probably emerged in evolution before the separation of animal, fungi, and plant kingdoms and originate from an anion/nucleotide or anion/anion transporter ancestor. Mammalian UCP1, UCP2, UCP3, and plant uncoupling proteins pUCP1 and pUCP2 are similar and seem to form one subgroup, whereas UCP4 and BMCP1 belong to a different group. Molecular, biochemical, and phylogenic data suggest that UCP2 could be considered as an UCP-prototype. UCP1 plays its biological role mainly in the non-shivering thermogenesis while the role of the other types is unknown. However, hypotheses have suggested that they are involved in the general balance of basic energy expenditure, protection from reactive oxygen species, and, in plants, in fruit ripening and seed ontogeny.
Keywords: Mitochondria; Uncoupling Protein 1; Membrane Proteins; Phylogeny; iontové kanály; fyziologie rostlin; Molecular Sequence Data; molekulární sekvence - údaje; termogeneze; mitochondrie; zvířata; Mitochondrial Proteins; mitochondriální proteiny; transportní proteiny; Amino Acid Sequence; uncoupling protein 1; Carrier Proteins; rostlinné proteiny; fylogeneze; Plant Physiological Phenomena; Plant Proteins; membránové proteiny; Ion Channels; Animals; Thermogenesis; terciární struktura proteinů; Protein Structure, Tertiary; sekvence aminokyselin